Mathematics pre- and post-pandemic comparison of emergent bilingual students by their special education status: A Texas statewide investigation - Torres, Erik; Slate, John R. (American Journal of STEM Education, 2025)
In this Texas multiyear investigation, the Grade 8 STAAR Mathematics performance of Emergent Bilingual students was examined by their special education status (i.e., enrolled in special education or not enrolled). Five years of data, two prior to the pandemic (i.e., 2017-2018, 2018-2019) and three years post-pandemic (i.e., 2020-2021, 2021-2022, and 2022-2023), were analyzed to ascertain the effects of the COVID-19 pandemic. In the two years prior to the pandemic, lower percentages of Emergent Bilingual students in special education met the three grade level standards than Emergent Bilingual students who were not in special education. After the pandemic, improved performance was present for both groups of Emergent Bilingual students. Specifically, more than 10% of Emergent Bilingual students in special education met the Meets Grade Level standard in the 2022-2023 school years, a 4% increase from the 2021-2022 school year, and a 7% increase from the 2020-2021 school year. Additionally, in the 2022-2023 school year, a higher percentage of both groups met the Approaches Grade Level standard and Meets Grade Level standard after the pandemic.